Evidências de temáticas presentes nos Projetos de Leis relacionadas ao direito das mulheres no legislativo amazonense - Ramos, Delyane de Sousa (Brasil, 2024)
Discusses legislative information based on evidence from Bills on women's rights. The objective of the research is to analyze the themes present in Bills related to women's rights in Amazonas and their relationship with women's life safety data, for this, the specific objectives are: Identify laws aimed at women's rights and their proponents over the past five years; categorize the themes identified in the Bills; collect official data to consider the most evident themes found in the Bills and present an overview of the themes, contextualizing them with official data on women's lives. As for the objectives, it is a descriptive and exploratory research, as for the procedures, it is an bibliographic and documentary research. The results obtained show an increase in the presence of women in the legislative sphere of Amazonas and show that safety and health are the thematic focus of proposed laws, as there is an increase in cases of violence against women. It is concluded that the indicators on people's quality of life, in this research, women in particular, reflect on the themes of proposed laws, so that parliamentarians seek to observe existing problems in order to solve them.